Transtheoretical model of change for weight control in Malaysian context - Chang, Ching Thon (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Obesity is a global problem, and the prevalence of obesity in Malaysia has increased four . folds during a 10 years period (1996 - 2006). Empirical support of the effectiveness of weight control using Transtheoretical Model of Change (TIM) as the framework have been demonstrated by some studies and clinical practice for weight control in developed countries. However, TIM's potentia1 in weight control has yet to be tested among the natives in Sarawak, Malaysia. This research study used focus groups and survey to evaluate the applicability of TTM for weight control in overweight and obese Bidayuh, Malay and Than adults in saraway Particularly, this study aimed to determine the applicability of the key constructs of TIM: Stages of Change, Self- Efficacy, Decisional Balance and Processes of Change in terms of stage distribution, factorial structure and the relationship between these constructs and the Stages of Change. A total of 271 respondents participated in the survey and 38 of these respondents joined the focus groups. The findings of this study indicated that the basic constructs of the TIM: the Stages of Change, the Decisional Balance, the Self-Efficacy, and the integration between the Stages of Change, and the Decisional Balance, Stages of Change and the SelfEfficacy variables were generalizable to the study population. The generalisability of Processes of Change was less clear. The Stages of Change algorithm was able to classify the respondents into different Stages of Change to lose weight. Although five items from the original Decisional Balance scale were deleted in the factor structure validation process, the remaining 15 pro and con items were able to discriminate the Decisional Balance variable of this study sample. Weight Efficacy Lifestyle Questionnaire (WELQ) was found to be applicable to measure Self-Efficacy construct of TIM. Scale validation obtained an I8-item, three subscales for WELQ. The generalisibility of Self- Efficacy to this population was also determined. Twenty-seven items of Processes of Change inventory were deleted during the factor structure validation process with many items of the original processes dispersed into different processes. As such, the relationship between Stages and Processes of Change in this study is less distinctive, making the generalisability of this construct less convincing. This research study found the focus groups and survey used in a concurrent mixed method approach was illuminating. The findings of the reasons for participants to remain in the Precontemplation Stage of losing weight were consistent with those proposed by the TIM.